Análise das estratégias de movimento adotadas durante a realização de manuseio de carga - Carregaro, Rodrigo Luiz (2007)
Despite recent technological advances, occupational activities of manual nature are still essential in many sectors and industries. Such activities impose risky conditions, which are inherent to its nature and can be responsible for musculoskeletal injuries. In addiction, the complexity and the interaction of risk factors, many still not comprehended, that act together during the performance of manual material handlings confer challenges and stimulations to the preventive approach. In this way, two main studies (Studies I and II) and two unfolding studies had been carried through. The main studies contextualized the hamstrings flexibility and its influence on the performance of occupational tasks. The objectives of Study I had been to compare the results of two clinical tests used to evaluate hamstrings flexibility and to evaluate the reliability of the photogrammetric procedure adopted for the analysis. The fingertip-to-floor test and straight leg raise test were applied in 35 healthy male subjects. Based on tests results, subjects were divided into two groups: normal and reduced flexibility. Superficial anatomical landmarks were fixed on bony references by means of manual palpation in order to permit the tracing of the hip, thoracic-lumbar, leg, knee and tibio-tarsal angles. The student t test was applied to evaluate the differences between the two groups, for each variable. Findings showed that hip angle was significant lower at the reduced flexibility group and that the straight leg raise test was more sensible for detecting subjects with reduced flexibility. The aim of Study II was to evaluate the influence of hamstrings flexibility on the movement strategy of the trunk and pelvis adopted by healthy subjects during the performance of the manual handling. Subjects were divided into two groups, based on the straight leg raise test. A JVC digital camera with a sampling of 50 frames/second and positioned perpendicularly to the sagittal plane of the subjects was used to register the activity. The cross-correlation coefficient was used to quantify movement patterns relationship between groups, and the student t test applied to the movement variables in order to determine differences between groups. The results had demonstrated that subjects with reduced flexibility used a lesser pelvic amplitude and bigger amplitudes of the trunk during handling. Still, subjects with reduced flexibility adopted a retroverted movement of the pelvis, without great alterations during the activity. The unfolding studies contextualized the comparison of the strategies adopted by subjects with experience in load handling activities and inexperienced individuals. The Study III had as objective to evaluate the manual handling performed by 16 experienced subjects and 15 inexperienced ones. It was used a flexible electrogoniometer to measure trunk movements and the University of Michigan 3D software to estimate the intradiscal compression in L5/S1 during the handling. The normalized movement patterns were evaluated and the coefficient of variation was applied to quantify the variability of this movement. The student t test determined the differences between variables. Results pointed out to great variability of adopted postures. Smaller amplitudes of flexion had been found, but bigger amplitudes of trunk extension when the loads were deposited, respectively, in low and high surfaces for experienced individuals. Experienced subjects presented lower intradiscal compression during box deposition and the lowering task was characterized by the highest intradiscal compression. Study IV aimed to compare manual handling strategies adopted by experienced and inexperienced subjects with relation to the positioning of the feet and trunk during lowering and inclination of the box during lowering and lifting activities. Ten experienced workers and 10 subjects without professional experience with the handling activity had been selected. The manual handling carried out between different heights was filmed. By means of one edition software, the images referring to the instant of 50% of the task had been selected and used to classify the postures and to measure the inclination of the box. An ANOVA with 3 factors was used to evaluate the inclination of the box with relation to the experience, handled load and type of handling (lifting and lowering). The results had indicated that subjects with professional experience adopted strategies characterized by biggest inclination of the box and adoption of balanced postures of the trunk, with widening of the support base. Professional experience determined the adoption of different movement strategies, when compared to inexperienced ones, in response to task conditions. However, other studies are suggested in order to determine if such strategies were protective or risky ones. The results presented in this dissertation raise the hypothesis that hamstrings flexibility is a risk factor for the increase of trunk overload, during the performance of manual material handling.